A Review on Synthesis and Characterization of Ag2O Nanoparticles for Photocatalytic Applications - Workneh M. Shume; H. C. Ananda Murthy; Enyew Amare Zereffa (Journal of Chemistry)
Even though the photocatalytic processes are a good technology for treatment of toxic organic pollutants, the majority of current photocatalysts cannot utilize sunlight sufficiently to realize the decomposition of these organic pollutants. As stated by various researchers, metal oxide nanoparticles have a significant photocatalytic performance under visible light source. Among various chemical and physical methods used to synthesize nanostructured silver oxide, green synthetic route is a cheaper and environmental friendly method. To confirm the optimum production of Ag2O NPs, effect of pH, extract concentration, metal ion concentration, and contact time were optimized. The structure, morphology, crystallinity, size, purity, elemental composition, and optical properties of obtained Ag2O NPs were characterized by different techniques, such as scanning electron microscopy (SEM), transmission electron microscope (HRTEM), X-ray diffraction (XRD), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR), and UV-visible spectrophotometer accordingly as revealed by our literature review. The photocatalytic performance of the synthesized nanocrystalline Ag2O by photocatalytic degradation of organic dyes under visible light irradiation has been discussed thoroughly in this review. Many past studies revealed that organic dyes and pollutants are decomposed completely by green synthesized Ag2O NPs under irradiation of visible light.